Bearing capacity and settlement of clay foundations under block cyclic loading - I. T. Mirsayapov; Hani Mohammed Abdo Sharaf (Vestnik MGSU)
Introduction. The available methods of assessment of bearing capacity by deformations of foundations mainly take into account single static loads of short duration or cyclic loads with unchanged values during the whole period of operation. The effect of cyclic loading of non-stationary regimes on the behavior of soil bases is practically not studied. In this connection, the research was carried out to develop a method for calculating the settlement of the bearing capacity of clay foundations under block cyclic loading.Materials and methods. To achieve the purpose of this paper, experimental studies of clay foundations in triaxial compression and tray test devices, as well as theoretical studies to determine the bearing capacity and settlement of clay foundations under different loading regimes were carried out.Results. On the basis of existing calculations of bearing capacity and settlement of foundations and the study of the behavior of clay soils under cyclic loads, the equations in compact form are obtained, which make it possible to take into account the peculiarities of deformation of clay soils significantly reducing the complexity and accuracy of the calculations. The development of methods for calculating the bearing capacity and settlement of clay foundations under block cyclic loads is at a sufficiently high level.Conclusions. A method for calculating the bearing capacity of clay foundations under block cyclic loading is proposed and an engineering method for calculating the settlement of clay foundations is developed, based on the method of layer-by-layer summation, which takes into account the simultaneous change in the spatial stress-strain state and mechanical characteristics of soils in the process of mode block cyclic loading.